Temperature control using PID gain scheduling method for glycerin bleaching process: article / Riduan Suluhi - Suluhi, Riduan
The aim of the study is to design and implement the temperature control using gain scheduling method for glycerin bleaching process. In the field of process control system, it is well known that the PID controller have proved their usefulness in providing satisfactory control. The PID controller is by far the most common control algorithm. Most feed-back loops are controlled by this algorithm or minor variation of it. The combination of P, I and D term will improve the process performance and enhance the process controllability. Gain scheduling is very easy to implement in computer controlled system. Gain scheduling is a method to find auxiliary variables that correlate well with the changes in process dynamics. Then the controller parameters are determined at a number of operating conditions based on the scheduling variables that have been deformed. In this study, the controller has tuned using ITAE tuning method and several operating condition of controller correspond to the process gain a developed. The performance of the system was evaluated in term of percentage overshoot (%OS), rise time (Tr) and settling time (Ts) by comparing the response obtain before and after gain scheduling implementation. The result revealed that the implementation of gain scheduling can improve the performance of glycerin bleaching process.